SPE Improved Oil Recovery Conference 2018
DOI: 10.2118/190302-ms
|View full text |Cite
|
Sign up to set email alerts
|

Foaming Behavior of CO2-Soluble, Viscoelastic Surfactant in Homogenous Porous Media

Abstract: Aqueous foam has been demonstrated through laboratory and field experiments to be a promising conformance control technique. This study explores the foaming behavior of a CO2-soluble, cationic, amine-based surfactant. A distinguishing feature of this surfactant is its ability to dissolve in supercritical CO2 and to form Wormlike Micelles (WLM) at elevated salinity. Presence of WLM led to an increase in viscosity of the aqueous surfactant solution. Our study investigates how the presence of WLM structures affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Ramadhan [136] investigated the foaming behavior of a CO 2 -soluble, cationic, aminebased surfactant, N.N.N'-trimethyl-N'-tallow-1,3-diaminopropane (DTTM), which forms wormlike micelles at elevated salinity. They believed that the viscous fingering of surfactantcarrying CO 2 causes a delay in foam generation and propagation.…”
Section: Supercritical Co 2 Foammentioning
confidence: 99%
“…Ramadhan [136] investigated the foaming behavior of a CO 2 -soluble, cationic, aminebased surfactant, N.N.N'-trimethyl-N'-tallow-1,3-diaminopropane (DTTM), which forms wormlike micelles at elevated salinity. They believed that the viscous fingering of surfactantcarrying CO 2 causes a delay in foam generation and propagation.…”
Section: Supercritical Co 2 Foammentioning
confidence: 99%
“…A CO 2 -soluble, cationic, amine-based surfactant has a distinguished feature of dissolving capacity in Sc-CO 2 and forming wormlike micelles (WMLs) at high salinity. The presence of WMLs led to an increase in the viscosity of the aqueous surfactant solution . In high-permeability formation and higher temperatures, a methyl quaternized erucyl amine is convenient for VES-based fracturing fluids .…”
Section: Introductionmentioning
confidence: 99%
“…They found that the use of VES in a sandstone reservoir increases the recovery by 25% and increases the recovery in carbonate reservoirs, but the efficiency depends on the wetting characteristics of the reservoir. The mobility of the foam can be improved using VES in CO 2 foam flooding (Farid Ibrahim and Nasr‐El‐Din, 2018; Ramadhan et al, 2018). The cocamidopropyl betaine showed excellent synergy with nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…A mixture of silica nanoparticles and cocamidopropyl betaine surfactant resulted a significant additional oil recovery due to better foam stability and mobility (Farid Ibrahim and Nasr‐El‐Din, 2018; Farid Ibrahim and Nasr‐El‐Din, 2019). The foam mobility improvement can be achieved by a certain class of VES that can dissolve in supercritical CO 2 and form wormlike micelles (Ramadhan et al, 2018). In summary, the VES have shown great potential as an alternate to both surfactants and polymers for EOR.…”
Section: Introductionmentioning
confidence: 99%